The outcomes and controversies of transplant tourism—Lessons of an 11-year retrospective cohort study from Taiwan - Tsai, Daniel Fu-Chang (PLoS One, 2017)
BACKGROUND: Transplant tourism has increased rapidly in the past two decades, accounting for about 10% of world organ transplants. However it is ethically controversial and discouraged by professional guidelines. We conducted this study to investigate the outcomes and trends of overseas kidney and liver transplantation in Taiwan to provide a sound basis for ethical reflection. METHODS AND FINDINGS: The Taiwanese National Health Insurance Research Database was used to identify 2381 domestic and 2518 overseas kidney transplant (KT) recipients from 1998 to 2009 and 1758 domestic and 540 overseas liver transplantation (LT) recipients from 1999 to 2009. Cox proportional hazards models were used to assess the risks of mortality and graft failure. The numbers of overseas transplantation increased after 2000, reached a peak in 2005 and decreased after 2007. Compared to their domestic counterparts, the overseas KT recipients were older, male predominant, with shorter pre-op dialysis period and more comorbidities. Similarly, the overseas LT recipients were older, male predominant and had more hepatocellular carcinoma cases. The 1-, 5-, and 10-year patient survival rates were 96.9%, 91.7% and 83.0% respectively for domestic KT and 95.8%, 87.8% and 73.1% for overseas KT (p<0.001). The 1-, 5-, and 10-year patient survival rates were 89.2%, 79.5%, 75.2% for domestic LT and 79.8%, 54.7%, 49.9% for overseas LT (p<0.001). CONCLUSION: The poorer outcomes of the overseas groups may be due to more older patients, more comorbidities (KT), or more hepatocellular carcinoma recurrences (LT). After domestic reform and international ethical challenges, the numbers of organ tourism decreased but the practice still persisted surreptitiously. Compulsory registration policies for overseas transplantation with international conventions to sanction organ trafficking and transplant tourism should be considered to stop these controversial practices.